Analisis Sentimen Media Sosial Pada Kasus Beach Club Raffi Ahmad Di Kawasan Ekosistem Unesco Kabupaten Gunungkidul - Ratna Puspita Sari; Rr. Tsabitah Phalozaky Anta Putri; Shahnez Annisa Mekoa; Riesta Ayu Oktarina; Edelweis Putri Prima (LPPM Stikosa-AWS, 2025)
The Raffi Ahmad Beach Club development project in the UNESCO ecosystem area of ​​Gunungkidul Regency has become a public discussion, especially on social media. Various opinions have emerged, both those supporting and opposing this project. This study aims to analyze public sentiment towards the project using a social media-based sentiment analysis approach. Data was collected from various social media platforms, such as Twitter, Facebook, and Instagram, using web scraping and API techniques. After that, the data was processed through the stages of text cleaning, tokenization, stemming, and removal of stopwords. The sentiment analysis methods used include lexicon-based approaches, machine learning (Naïve Bayes, SVM, Random Forest), and deep learning (LSTM, BERT) to identify the polarity of public opinion (positive, negative, or neutral). The results of the study show that there is significant polarization of opinion regarding the Beach Club project. The majority of negative sentiments are related to concerns about environmental impacts and ecosystem sustainability, while positive sentiments focus on the potential for increasing the local economy and tourism. In addition, it was found that factors such as media coverage, statements by public figures, and the dynamics of online discussions influence public perceptions of this project. The findings of this study can be a reference for local governments and stakeholders in designing more sustainable development policies and considering public opinion in decision making.